Bidentate ligand-catalyzed enantioselective addition of RZnX to benzaldehyde - Jagtap, Ravindra S.; Joshi, Navalkishore N. (Tetrahedron Letters, 2011)
{Enantioselective addition of RZnX (R = alkyl
Keywords: 1; 2-Addition; Asymmetric synthesis; Chelating ligands; Organozinc

Improved synthesis and resolution of cis- and trans-2,3-diphenyl morpholines - Jagtap, Ravindra S.; Joshi, Navalkishore N. (Tetrahedron-Asymmetry, 2011)
An improved procedure for the synthesis of cis- and trans-2,3-diphenyl morpholines with good overall yield is described. The stereoisomers were efficiently resolved through the corresponding diastereomeric salts using tartaric acid and (R)-mandelic acid. (C) 2011 Elsevier Ltd. All rights reserved.